IMPLEMENTASI PROGRAM EDUKASI MITIGASI BENCANA DALAM MENINGKATKAN PENGETAHUAN MASYARAKAT MENGHADAPI BENCANA BANJIR PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA SURAKARTA TAHUN 2023 - Putri, Aktiffiani Energi; Haryanto, Aris Tri (Solidaritas, 2025)
The Surakarta City Government is committed to promoting disaster mitigation education programs, the government and local governments are responsible for implementing disaster management. The implementation of this flood disaster education program is carried out by the Surakarta City Regional Disaster Management Agency. This study aims to describe the implementation of the flood disaster mitigation education program. This study uses the theory of George C. Edward III's Policy Implementation. This type of research is descriptive qualitative, the types of data used are primary data and secondary data, the determination of informants using purposive sampling techniques. Data collection techniques used in this study are observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the Surakarta City Regional Disaster Management Agency always strives to implement Law of the Republic of Indonesia Number 24 of 2007 concerning Disaster Management, but there are obstacles in the form of policy communication where information has not been conveyed clearly, triggering problems regarding public knowledge in dealing with flood disasters. As for suggestions for the above problems, the community is expected to follow the flood disaster mitigation education program that is being held and the community is asked to be more active in carrying out independent evacuation measures if a disaster occurs before assistance arrives. Keywords: implementation, flood disaster mitigation